Evaluation of an integrated intervention to reduce psychological distress and intimate partner violence in refugees: Results from the Nguvu cluster randomized feasibility trial. - M Claire Greene (Public Library of Science (PLoS), 2021)
Introduction The complex relationship between intimate partner violence and psychological distress warrants an integrated intervention approach. In this study we examined the relevance, acceptability, and feasibility of evaluating a multi-sectoral integrated violence- and mental health-focused intervention (Nguvu). Methods We enrolled 311 Congolese refugee women from Nyarugusu refugee camp in Tanzania with past-year intimate partner violence and elevated psychological distress in a feasibility cluster randomized trial. Women were recruited from local women's groups that were randomized to the Nguvu intervention or usual care. Participants from women's groups randomized to Nguvu received 8 weekly sessions delivered by lay refugee incentive workers. Psychological distress, intimate partner violence, other wellbeing, and process indicators were assessed at baseline and 9-weeks post-enrollment to evaluate relevance, acceptability, and feasibility of implementing and evaluating Nguvu in refugee contexts. Results We found that Nguvu was relevant to the needs of refugee women affected by intimate partner violence. We found reductions in some indicators of psychological distress, but did not identify sizeable changes in partner violence over time. Overall, we found that Nguvu was acceptable and feasible. However, challenges to the research protocol included baseline imbalances between study conditions, differential intervention completion related to intimate partner violence histories, differences between Nguvu groups and facilitators, and some indication that Nguvu may be less beneficial for participants with more severe intimate partner violence profiles. Conclusions We found evidence supporting the relevance of Nguvu to refugee women affected by partner violence and psychological distress and moderate evidence supporting the acceptability and feasibility of evaluating and implementing this intervention in a complex refugee setting. A definitive cluster randomized trial requires further adaptations for recruitment and eligibility screening, randomization, and retention. Trial registration ISRCTN65771265, June 27, 2016.